Exploring millennial researcher ethical decision model: Towards using a psychoanalytic approach - Abdul Ghani Azmi, I. (2015)
Abstract—Generational factor is significantly important because Millennials are more ambitious, confident, independent, and achievement-oriented and thus, created generational differences in ethical choice as a conscientious moral agent and how to act to maximize outcome. Due to these characteristics, the Millennials are found to be less ethical reasoning tolerant. Accordingly, this proposed study is to synthesize the underlying factors of ethical decision making in millennial researchers. With interest in understanding the ethical framework used by millennial researcher, this research will explore into the characteristics of the millennial and focus on the integration of moral development and theory of reasoned action to support the third thrust of National Higher Education Strategic Plan (NHESP) wherein to enhance research and innovation.